Produção de enzimas ligninolíticas a partir de um processo fermentativo em efluente têxtil por Phanerochaete chrysosporium - Ricaczeski, Cecilia Claudete (2020)
Effluents are a challenge for the textile industries, as they cannot be released into the environment without proper treatment. Biodegradation has been increasingly explored as an alternative for the treatment of this type of effluent, allowing the coproduction of molecules of commercial interest. The purpose of this work is to evaluate the production of lignin peroxidase and manganese peroxidase enzymes from a textile effluent using the fungus Phanerochaete chrysosporium. The results of the work indicated an activity of 15.32 U.L-1 for manganese peroxidase and 70 U.L-1 for lignin peroxidase. Demonstrating that the studied process is promising for the production of ligninolytic enzymes from a supplemented textile effluent. These enzymes can later be used in the textile manufacturing process to reduce the hydrogen peroxide used in the bleaching process and they can also be used after dyeing, to reduce residual dyes, adding sustainability and fostering a circular economy.